2022
DOI: 10.55365/1923.x2022.20.76
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Tax Administration, Macroeconomic Stability and Economic Growth: Assessment and Interaction

Abstract: The article deals with investigating the link between the quality of tax administration, macroeconomic stability and economic growth. The paper identifies the benefits and risks of the shadow operations for macroeconomic stability of the country. Based on the analysis of indicators of the effectiveness of tax policy implementation, an approach to assessing the quality of tax administration of the country was proposed. Based on empirical calculations, a conclusion about the low quality of tax policy in the coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…ness of choosing GDP growth as a key indicator of economic dynamics is confirmed by numerous studies(Tahat, 2023; Maris, 2022; Shafizada & Aslanova, 2022; Bilan et al, 2020; Vasilyeva et al, 2021).To improve the accuracy of modeling, control variables are integrated into the model, including agricultural land (% of land area), general government final consumption expenditure (% of GDP), gross fixed capital formation (% of GDP), and trade (% of GDP). The rationality of choosing such a set of control variables is confirmed by Lyulyov et al (2021) andZolkover et al (2022). The modeling results allow formalizing the impact of the inflation rate on the economic growth indicator in the short and long term for the entire panel of post-Soviet countries.Stage 3 is a determination of individual coefficients characterizing the relationship between the dynamics of inflationary processes and parameters of economic growth using least squares regression modeling in the Stata 14.2/SE software product.…”
mentioning
confidence: 61%
“…ness of choosing GDP growth as a key indicator of economic dynamics is confirmed by numerous studies(Tahat, 2023; Maris, 2022; Shafizada & Aslanova, 2022; Bilan et al, 2020; Vasilyeva et al, 2021).To improve the accuracy of modeling, control variables are integrated into the model, including agricultural land (% of land area), general government final consumption expenditure (% of GDP), gross fixed capital formation (% of GDP), and trade (% of GDP). The rationality of choosing such a set of control variables is confirmed by Lyulyov et al (2021) andZolkover et al (2022). The modeling results allow formalizing the impact of the inflation rate on the economic growth indicator in the short and long term for the entire panel of post-Soviet countries.Stage 3 is a determination of individual coefficients characterizing the relationship between the dynamics of inflationary processes and parameters of economic growth using least squares regression modeling in the Stata 14.2/SE software product.…”
mentioning
confidence: 61%
“…Leonov et al (2012) and Vasylyeva et al (2014) also confirm that lack of institutional capacity significantly constrains the development of the investment segment of the financial market. Fiscal policy inefficiency and extremely high fiscal burden are also mentioned within obstacles that eliminate green economic growth outcomes as a response to investment inputs (Lyulyov et al, 2021;Zolkover et al, 2022). Filipava and Murshudli (2023) focus on the role of private financial institutions in sustainable development issues, including the major investment banks and companies, several European financial centers, London (Green Finance Initiative), Luxembourg (Green Exchange), and Paris (Finance for Tomorrow Initiative), and stock exchanges (in Dublin, Milan, Stockholm, and Frankfurt), as well as informal green associations in corporate and financial sectors (mutual obligations platforms, joint industry initiatives, lobby groups).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The evolutionary path of the development of the financial system, its interdisciplinary nature and connection with other sectors prove the decisive role of financial stability in ensuring the stability of economies (Njegovanović, 2023). It has been empirically confirmed that the quality of regulation and administration is the basis for ensuring macroeconomic stability (Zolkover et al, 2022). A country's economic growth largely depends on the impact of inflation, foreign exchange rates and interest rates (Sinaga, 2022;Kashcha & Dun, 2022;Adama et al, 2022;Aiyedogbon et al, 2022), and this influence is intensified in crisis conditions.…”
Section: Introductionmentioning
confidence: 99%